Understanding teams - Neider, Linda L., 1953-; Schriesheim, Chester (Emerald Publishing Limited : Information Age Pub., 2005)
Mark Twain, the great American writer, once stated that synergy is the bonus achieved when things work together harmoniously. Organizations in the twenty-first century are driven by a need to achieve synergy for all of their various processes, and organizational structures such as teams have become one of the major ways to do so. Thus, the fourth volume of Research in Management is devoted to highlighting conceptual frameworks and research investigations which elucidate factors related to effective team processes and those which may, in fact, hinder effectiveness.
Keywords: Teams in the workplace.; Business & Economics -- Management.; Management and management techniques.; elektronické knihy; electronic books